From Sukabumi to Amsterdam 1883: Sundanese Society through Parakansalak Tea Plantation Exposition - Asep Nugraha (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
In 1883 the tea plantation in the Parakansalak Sukabumi region brought workers from the local plantation community to Amsterdam, to participate in De Internationale Koloniale en Uitvoerhandel Tentoonstelling. The planter, Mr. Holle, promoted the commodity of tea by including the original culture of the colony's land, precisely the Sundanese ethnicity. Sundanese cultural presentations include gamelan and dance performances and cultural tours of Sundanese society. Europeans directly witnessed people from the colonies playing music and dancing and carrying out daily life activities through village society. This paper describes the existence of the Sundanese society through the Parakansalak plantation group in Amsterdam in 1883, uses a qualitative approach with literature studies, and focuses on situational analysis that examines the activities of the Sundanese people through the Parakansalak tea plantation group at the Exposition Activity in 1883. The purpose of this study was to determine the impact of the existence of the Sundanese people in a new place - in Amsterdam - Europe by introducing Sundanese culture during the Exposition activity. The results obtained were the astonishment of the European community who saw the culture of the colonized nation. The first impression, Europeans see a group of Sundanese people who practice low and primitive culture. Still, it united people of different religions, ethnicities, and skins to fundraising for the Mount Krakatoa disaster in the Dutch East Indies.